2018
DOI: 10.1242/jeb.184713
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of morphology and ultrastructure of hearts among wild African antelope

Abstract: The hearts of smaller mammals tend to operate at higher mass-specific mechanical work rates than those of larger mammals. The ultrastructural characteristics of the heart that allow for such variation in work rate are still largely unknown. We have used perfusion-fixation, transmission electron microscopy and stereology to assess the morphology and anatomical aerobic power density of the heart as a function of body mass across six species of wild African antelope differing by approximately 20-fold in body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…That our capillary and mitochondrial density exponents are similar indicates parallel scaling of these two traits as a function of body mass across almost the full range for terrestrial mammals (figure 2). A parallel scaling between cardiac capillary supply and mitochondrial investments was previously shown across six species of different-sized adult wild African antelope where, relative to the cardiomyocyte reference space, the capillary numerical density matched the mitochondrial inner membrane surface density [1]. In this earlier study for a single family of mammals, the negative exponents were somewhat steeper ( ca –0.15) than in the present study assessing general mammalian trends, highlighting that patterns observed within phylogenetic groups do not necessarily translate across all mammals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…That our capillary and mitochondrial density exponents are similar indicates parallel scaling of these two traits as a function of body mass across almost the full range for terrestrial mammals (figure 2). A parallel scaling between cardiac capillary supply and mitochondrial investments was previously shown across six species of different-sized adult wild African antelope where, relative to the cardiomyocyte reference space, the capillary numerical density matched the mitochondrial inner membrane surface density [1]. In this earlier study for a single family of mammals, the negative exponents were somewhat steeper ( ca –0.15) than in the present study assessing general mammalian trends, highlighting that patterns observed within phylogenetic groups do not necessarily translate across all mammals.…”
Section: Discussionmentioning
confidence: 90%
“…The evolution of heart size among mammals of increasing body mass is explained primarily by the large increase in volume loads that act upon the walls of the ventricles in larger species [1], and secondarily by the subtle increase in central arterial blood pressures in larger and taller terrestrial species [24]. According to the Principle of Laplace, the increase in volume and pressure loads necessitate an increase in cardiac wall thickness so that wall stress is conserved [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, comparative anatomical data should be generated by a team of investigators within a defined period of time, under standardized conditions (in the habitat considered the typical for the species, during a period of either optimal or limiting resource availability), on a consistent number of specimens of each species considered, recording not only body mass but less condition‐dependent proxies for body size. Such an approach is feasible for concise questions limited to species of a specific region (e.g., Snelling et al, ), but is much more difficult to achieve on a global level.…”
Section: Discussionmentioning
confidence: 99%